Carcass and tissues composition at Turopolje Pig Breed – Autochthonous Croatian Breed - Đikić, Marija; Salajpal, Krešimir; Karolyi, Danijel; Čubrić Čurik, Vlatka; Đikić, Domagoj; Mihelčić, M.; Rupić, V.; Jurić, Ivan (Acta Agraria Kaposváriensis, 2006)
In Turopolje pig breed the carcass and tissues composition was established by analyzing the share of muscle (M), fat (F) and bone (B) tissues in the carcass and the chemical content (water, W, protein, P, lipid, L, ash, A) of the back fat and m. longissimus dorsi (MLD). Also, the some histochemical characteristics (diameter and proportion) of slow-twitch high-oxidative (SO), fast-twitch oxidative-glycolitic (FOG), and fast-twitch glycolitic (FG) fibre types of MLD were analyzed. Investigation was carried out on Turopolje breed pigs (n = 10, age 679 ± 20 days and 100.3 kg ± 4.9 kg). Pigs were fattened in the outdoor system of flood forests and marsh meadows biocenosis (Quercus robur and Deschampsietum caespitosae) according to traditional Croatian technology of low input feed (0.5 kg of corn seed/day/animal) in ecosystem. On the slaughter line the animals and carcasses were separately weighted and cut according to Weniger (1963) method and by total dissection. The samples of muscle and fat from the left side at the last rib level were taken after chilling 24 h at +4 °C and stored at -20 °C until chemical analysis. For histochemical analysis, sample from the same place and about 1 cm wide were taken 30 min after slaughter and frozen in liquid nitrogen until analysis. At Turopolje pig breed in the cold carcass (79.7 kg) were estimated the share of tissues respectively: M, 40.5%; F, 33.8%; B, 9.7% and share of the lard (4.0%) and double chain (3.2%). The chemical contents of MLD and back fat were respectively: W, 74.71% and 7.25; P 21.19% and 1.49; F, 1.46% and 91.76% and A, 1.06 and 0.06. The size and proportions of fibre types in MLD were respectively: SO, 38.9 µm and 10.5%; FG, 57.7 µm and 52.9%; FOG, 53.5 µm and 36.7%.
Keywords: Turopolje pig; carcass; tissue chemical content; fibre type